Termination of Employment (PHK) and its Impact on Workers - Dedi Aringga, Rino; Arafat Saputra, Agung; Meuraksa, M. Amin El Walad Meuraksa (Journal of Law and Humanity Studies, 2024)
Termination of Employment (dismissal) is one of the policies that can be implemented by companies as a last resort to address various issues, such as performance decline, operational efficiency, or financial difficulties. However, the implementation of dismissal must comply with the procedures stipulated in the Labor Law to ensure fairness for employees and avoid potential legal claims. This article discusses the dismissal procedures in accordance with labor regulations, the social and economic impacts of dismissal on employees, as well as the implications for communities affected by increased unemployment and economic instability. This study also examines solutions that can be implemented by companies to minimize the negative impacts of dismissals